Ostermarsch Ruhr '82 - Keine neuen Atomraketen in unserem Land. Kampf dem Atomtod. 10. - 12.4. Duisburg, Essen, Bochum, Dortmund - Jellema, Olaf; Ostermarsch-Komitee Ruhr, Dortmund; Plambeck & Co Druck und Verlag GmbH, Neuss
Bemerkungen: Archivstempel